Fiscal and economic impacts of a limited financial transaction tax. Final report: Research project conducted on behalf of the parliamentary group of the SPD - Dorothea Schäfer (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
The present study examines the effects of the introduction of a financial transaction tax along with enhanced cooperation across 11 European Union member states. In particular, based on the tax concept of the European Commission, the tax revenues for four participating countries, Germany, France, Italy, and Austria, are estimated. [...] – – Die vorliegende Studie untersucht die Wirkungen der Einführung einer Finanztransaktionssteuer im Rahmen einer verstärkten Zusammenarbeit von 11 Staaten der Europäischen Union. Insbesondere werden auf der Grundlage des Steuerkonzepts der Europäischen Kommission die Aufkommen für vier beteiligte Länder, Deutschland, Frankreich, Italien und Österreich, geschätzt. [...]
urn:nbn:de:0084-diwkompakt_2015-0963
Keywords: 330